A Walking Curriculum: From “Good Ideas for Walks” to Transformative Design for Eco-Social Change - Judson, Gillian; Datura, Michael (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2023)
This pilot implementation study examines the experiences of ten teachers who have employed a place-based learning resource called A Walking Curriculum for one to three years. A Walking Curriculum is an example of Imaginative Ecological Education—a pedagogical approach that centralizes imaginative engagement, emotional connection, and somatic understanding in place-based learning. Initially, researchers sought to understand teachers’ practices and to determine how (or if) A Walking Curriculum provided teachers with a deeper insight into the principles of Imaginative Ecological Education underlying it. The research focus shifted to the nature of professional development and the meaning of educational change in a more-than-human world. This article considers policy implications of an ecological model of educational change that might better align with the eco-social transformation intentions of Imaginative Ecological Education.